Peran Pastoral Gereja Dalam Menanamkan Nilai-Nilai Kristiani Tentang Self-Image Kepada Remaja Kristen - Gery Altobely Seroh (JURNAL TRANSFORMASI: Jurnal Teologi dan Kepemimpinan, 2022)
Self-image is an important thing that every human being must own. Because by having the right and proper self-image, then a person will be able to project him/herself correctly and precisely as well. It is not surprising that when a teenager has a good self-image, he/she will live a productive life or at least know how to appreciate his/herself well. It is not infrequently due to a bad or low self-image, one will live a life that is unproductive and tends to have low fighting power, and is even more likely to consider itself useless. Of course, this will have an impact on what will happen in the future. Seeing this phenomenon, we need an institution or group that can provide an understanding of self-image. The church and its pastoral practice are one way to instill Christian values ​​about self-image in youth. It is hoped that with these pastoral assistance activities, the youth will have a good and appropriate self-image. The writing of this scientific paper uses the literature research method, namely where the written sources used can provide the right contribution to the values ​​of self-image according to Christian values. This research can be a contribution to the church in its pastoral activities for youth because it is very relevant both theoretically and practically in instilling Christian values ​​about self-image.